Pendamping Literasi Keuangan dan Inovasi Produk Untuk Optimalisasi UMKM Sapu Lidi Melalui Program KKN di Desa Perkebunan Maryke - Reza Aliyanda; Amanda Putri Syahbana; Amri Muazib (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Community Service (KKN) in Perkebunan Maryke Village, Kutambaru District, Langkat Regency, was carried out by students of the Muhammadiyah University of North Sumatra from 12 to 27 August 2024. This program aims to improve the financial literacy of the community and optimize the potential of the broomstick MSME which is the main source of income for village residents. Through MSME mentoring activities, students conduct value chain analysis to improve production efficiency, product innovation, and more effective marketing strategies. This mentoring aims to increase the competitiveness of MSMEs and shorten distribution channels to a wider market. In addition, the financial literacy program in collaboration with Bank Sumut is also provided through workshops to teach the community, especially the younger generation, about the importance of saving, financial planning, and personal budget management. The results of this activity show an increase in community understanding of financial literacy and MSME management, as well as the creation of new innovations in broomstick products. This activity not only has an impact on increasing residents' income, but also strengthens social cohesion and sustainable village economic development. This program is expected to be a model for community empowerment in other rural areas.